Comparison of times recorded in the 60 m flat and the 60 m hurdles finals at the junior III national indoor championships 2010 and 2011 - Rata, B. C.; Rata, G.; Alexe, D. I.; Sava, A. (Journal of Physical Education and Sport, 2011)
The aim of this comparative study was to point out the dynamics of results in male and female athletes at the 60m flat and 60m hurdles events, heats and finals, of the Junior III National Indoor Championships carried out in March 2010 and March 2011. We took into account the results recorded during the finals of the 2010 and 2011 indoor competitions for Juniors III. In conducting the research we used the following methods: bibliographical study, test, statistical-mathematical and graphical method, and comparative analysis. The approach of this research was to examine the hypothesis that the dynamics of results with girl and boy juniors III during the speed events is an increasing one. The research included 64 athletes who were finalists in the 2010 and 2011 60m flat and 60m hurdles events at the Junior III National Championships which took place in Bacau. The results recorded for two consecutive years were tabulated, processed and analysed and highlighted the dynamics of results recorded by the finalists and the dynamics of participation in competition as well. The values recorded in girls and boys` 60m flat and 60m hurdles events showed that the average time in the final race was better in the previous year race. The conclusions of the study are that the in girls` 60m flat and boys`60m flat races the times recorded by the winners are better in the 2010 final (8.00s -girls; 7.35s - boys) than those in 2011 (8.03s -girls; 7.41s - boys). In the 60m hurdles races the winners` times are better in 2011 (9.34s -girls; 8.80s - boys) than in 2010 (9.36s -girls; 8.86s - boys). It was also noticed that the dynamics of results for those two years has an increasing trend only for the girls and boys` 60m hurdles event, therefore the hypothesis is only partially confirmed. Year after year there are a lot of retirements of young athletes therefore there is no continuity at this level and those who obtain best results in the heats do not get first place in the final. These findings require increased attention during the training process.